Sorafenib in patients with hepatocellular carcinoma: results of the observational INSIGHT study - Ganten, Tom M.; Koschny, Ronald (Clinical cancer research, 2017)
Purpose: Sorafenib is the only currently approved systemic therapy for advanced hepatocellular carcinoma (HCC). We aimed to evaluate the safety and efficacy of sorafenib therapy in patients with HCC under real-life conditions regarding patient, tumor characteristics, and any adverse events at study entry and at follow-up visits every 2 to 4 months. Experimental Design: The current INSIGHT study is a noninterventional, prospective, multicenter, observational study performed in 124 sites across Austria and Germany between 2008 and 2014. Results: Median overall survival and time to progression (RECIST) were found to be dependent on baseline Barcelona Clinic Liver Cancer (BCLC) tumor stage (A: 29.2, B: 19.6, C: 13.6, D: 3.1 and A: 6.0, B: 5.5, C: 3.9, and D: 1.7 months, respectively), Child-Pugh liver function (A: 17.6, B: 8.1, C: 5.6 and A: 5.3, B: 3.3, C: 2.5 months, respectively), and performance status of the patient; however, age did not affect prognosis. Sorafenib-related adverse events at any grade occurred in 64.9% of patients, with diarrhea (35.4%), hand-foot-skin reaction (16.6%), nausea (10.3%), and fatigue (11.2%) occurring most frequently. Conclusions: Sorafenib treatment was shown to be effective in a real-life setting, in agreement with previously reported clinical trial data. The therapy was found to have an acceptable safety profile, with predominantly mild to moderate side effects. Clin Cancer Res; 23(19); 5720-8. ©2017 AACR.
Gesehen am 15.06.2018